Relationship Between Vitamin D Supplementation and Improvement in Body for Carcinogenesis: A Literature Review - Irawan Sastradinata; Rizal Sanif; Cindy Kesty; Siti Hardianti Harahap (HM Publisher, 2022)
Vitamins are probably the best-selling dietary supplements in the United States, in which an estimated 35% of the population take multivitamin and mineral supplements. Data relating microconstituents to carcinogenesis are extremely limited, as explained in the first report. A striking feature of many of the compounds in the three groups mentioned above is their capacity to prevent or retard the occurrence of neoplasia. However, there is a paucity of data concerning the conditions under which inhibition occurs, the mechanisms of inhibition, and the precise impact of these microconstituents on humans. A literature review was conducted in the electronic databases PubMed and Google Scholar using the index terms